Additional benefits of belimumab in chronic phase of systemic lupus erythematosus and efficacy of tacrolimus combination therapy - Satoshi Suzuki; Tomoya Otani; Keigo Ikeda; Naoto Tamura; Shinji Morimoto (Immunological Medicine)
Systemic lupus erythematosus (SLE) is a typical autoimmune disease; although severe disease and refractoriness to existing therapies are still experienced, the number of cases resistant to remission induction has decreased with the establishment of various therapies. However, improving long-term prognosis remains a challenge due to the unavoidable prolonged use of non-selective glucocorticoids. To investigate the additional effect of belimumab in the chronic phase, we included 28 of 46 patients with SLE who were initiated on belimumab between January 2018 and October 2022 for glucocorticoid reduction. The efficacy of tacrolimus and mycophenolate mofetil in combination with belimumab was also compared. In the stable chronic phase, the combination with belimumab improved the SLE Disease Activity Index and reduced glucocorticoid requirement. The tacrolimus with belimumab group was not significantly inferior to the mycophenolate mofetil with belimumab group and was effective in treatment and glucocorticoid sparing including cases at all phases of SLE. To improve the long-term prognosis of SLE, it is crucial to introduce highly selective biological agents and reduce glucocorticoids whenever possible. Belimumab is effective with or without hydroxychloroquine and Tac was effective as concomitant drugs.